The prognostic value of elevated matrix metalloproteinase-9 in patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction: A two-year prospective study - Mustafa Umut Somuncu; Hamdi Pusuroglu; Huseyin Karakurt; İsmail Bolat; Seda Tukenmez Karakurt; Ali Riza Demir; Nilgun Isıksacan; Ozgur Akgul; Ozgur Surgit (Revista Portuguesa de Cardiologia, 2020)
Introduction: Increased matrix metalloproteinase-9 (MMP-9) levels in ST-elevation myocardial infarction (STEMI) are well established; however, existing data on MMP-9 values as a prognostic marker after STEMI are limited and have been conflicting. Objective: This study aimed to assess the clinical significance of MMP-9 in predicting two-year adverse cardiovascular events in patients who underwent primary percutaneous coronary intervention (PCI) after STEMI. Methods: In this prospective study, 204 patients with STEMI undergoing PCI were included. Participants were classified as high MMP-9 (n=102) or low MMP-9 (n=102) based on a cutoff of 12.92 ng/ml. Both groups were assessed at one and two years after STEMI. Results: Higher cardiovascular mortality at one year was observed in the high MMP-9 group (13.7% vs. 4.9% in the low MMP-9 group, p=0.03). When the follow-up period was extended to two years, the difference in cardiovascular mortality between the groups was more significant (17.6% vs. 4.9%, p=0.004). There was no significant difference at one-year follow-up in rates of advanced heart failure, however at the end of the second year, advanced heart failure was more prevalent in the high MMP-9 group (16.7% vs. 5.9%, p=0.015). After adjustment for potential confounders, a high MMP-9 value had 3.5-fold higher odds for cardiovascular mortality at two-year follow-up than low MMP-9. Conclusion: These results suggest that high MMP-9 levels are a strong predictor of cardiovascular mortality and advanced heart failure at two-year follow-up in STEMI patients. Resumo: Introdução: A elevação das metaloproteinases de matriz 9 (MPM-9) no enfarte do miocárdio com supradesnivelamento do segmento ST (EAMCSST) está bem estabelecida; no entanto, os dados existentes relativos aos valores de MPM-9 como marcadores de prognóstico após o EAMCSST são limitados e contraditórios. Objetivo: Avaliar o significado prognóstico das MPM-9 em eventos cardiovasculares a dois anos nos doentes submetidos a intervenção coronária percutânea primária (ICP) após EAMCSST. Métodos: Neste estudo prospetivo, foram incluídos 204 doentes com EAMCSST submetidos a ICP. Os participantes foram agrupados no grupo de MPM-9 elevadas (n=102) ou no grupo de MPM-9 baixas (n=102) com base no valor MPM-9 de 12,92 ng/ml. Ambos os grupos foram avaliados a um e a dois anos após EAMCSST. Resultados: A mortalidade cardiovascular mais elevada a um ano foi observada no grupo de MPM-9 elevadas (13,7% versus 4,9% no grupo com valores baixos, p=0,03). Quando o período de seguimento foi prolongado a dois anos, a diferença na mortalidade cardiovascular foi ainda superior (17,6% versus 4,9%, p=0,004). Não houve diferenças significativas no seguimento a um ano relativamente à insuficiência cardíaca avançada, mas no fim do segundo ano a insuficiência cardíaca avançada foi superior no grupo com MPM-9 elevadas (16,7% versus 5,9%, p=0,015). Após o ajuste para potenciais fatores confundentes, a presença de MPM-9 elevada aumentou 3,5 vezes a probabilidade de mortalidade cardiovascular no segundo ano de seguimento. Conclusão: Níveis elevados de MPM-9 constituem um importante fator preditor da mortalidade cardiovascular e da insuficiência cardíaca avançada num período de dois anos após EAMCSST.